Предмет: Алгебра, автор: mishenina98

Помогите... в универ надо

Приложения:

Ответы

Автор ответа: sedinalana
0
1
(3a ^{1/6} -2b ^{1/6} )(a ^{1/6} -b ^{1/6} )(a ^{1/6} +b ^{1/6} )-3/(a ^{1/6} +b ^{1/6} )=(3a ^{1/6} -2b ^{1/6} -3a ^{1/6} +3b ^{1/6} )(a ^{1/3} -b ^{1/3} )=b ^{1/6} /(a ^{1/3} -b ^{1/3} )
2
b ^{1/6} /(a ^{1/3} -b ^{1/3} )*b ^{5/6} /(a ^{2/3} +(ab) ^{1/3} +b ^{2/3} )=b/(a-b)
a=3,9  b=2,6
2,6/(3,9-2,6)=2,6/1,3=2
Автор ответа: mishenina98
0
Спасибо большое
Похожие вопросы
Предмет: Русский язык, автор: zaharovasonia2704201